Recent Chemical and Chemoenzymatic Strategies to Complex-Type N-Glycans - Zhao, Xiaoya; Huang, Yan; Zhou, Siai; Ao, Jiaming; Cai, Hui; Tanaka, Katsunori; Ito, Yukishige; Ishiwata, Akihiro; Ding, Feiqing (Frontiers in Chemistry, 2022)
Glycosylation is one of the major forms of protein post-translational modification. N-glycans attached to proteins by covalent bonds, play an indispensable role in intercellular interaction and immune function. In human bodies, most of the cell surface glycoproteins and secreted glycopeptides are modified with complex-type N-glycans. Thus, for analytical or medicinal purposes, an efficient and universal methods for obtaining homogeneous complex-type N-glycans have been an urgent need. Despite the extreme complicated structures, tremendous progresses of the synthesis of N-glycans have been achieved in detail. On one hand, chemical strategies have been shown to be effective to prepare core oligosaccharides of N-glycans with focusing at stereoselective glycosylations such as -mannosylation and -sialylation as well as methodology of the N-glycan assembly. On the other hand, chemoenzymatic strategies have also become increasingly powerful, drawing more and more attentions in recent years. This review attempts to highlight the very recent advancements in chemical and chemoenzymatic strategies to eukaryotic complex-type N-glycans.